Market integration of local energy systems: Is local energy management compatible with European regulation for retail competition?. (1st November 2016) - Eid, Cherrelle; Bollinger, L. Andrew; Koirala, Binod; Scholten, Daniel; Facchinetti, Emanuele; Lilliestam, Johan; Hakvoort, Rudi
Abstract: The growing penetration of distributed energy resources is opening up opportunities for local energy management (LEM) – the coordination of decentralized energy supply, storage, transport, conversion and consumption within a given geographical area. Because European electricity market liberalization concentrates competition at the wholesale level, local energy management at the distribution level is likely to impose new roles and responsibilities on existing and/or new actors. This paper provides insights into the appropriateness of organizational models for flexibility management to guarantee retail competition and feasibility for upscaling. By means of a new analytical framework three projects in the Netherlands and one in Germany have been analysed. Both the local aggregator and dynamic pricing projects present potentials for retail competition and feasibility of upscaling in Europe. Highlights: Diverse flexibility management approaches exist with trading arrangements. Horizontal organizational structures at distribution increase complexity. A single actor or settled price mechanism is preferred in Europe. An alternative to retail competition could be self-regulation.